Hypertension Prevention and Control Program - T Aghajani; T Samavat; M Haghazali; A Hodjatzadeh; M Najmi; N Ajang (Tehran University of Medical Sciences, 2009)
To control hypertension in Iran, one of the most preventable diseases, a program was established in rural areas of the country, employing the main strategy of people screening aged 30 years old and above, confirmation of suspected cases, offering cares and follows up. This program is integrated in the primary health care system at rural areas. An evaluation system embedded in the program, helps collecting data on main variable defined, including new cases and care taken. According to the results, the defects of the program are mainly categorized as education and referral system accessibility.